Dinoprostone Use and Rupture of Uterus in Primigravida: A Report of Two Cases - Upadhyaya, I (Nepal Journal of Obstetrics and Gynaecology, 2012)
Two cases of complete and incomplete uterine rupture following the use of dinoprostone gel for induction of labor (IOL) at 41 weeks of pregnancy in primigravidas; one of the two being diagnosed after vaginal delivery is presented herewith to alert cautious use of this important agent. NJOG 2011 Nov-Dec; 6 (2): 49-50 DOI: http://dx.doi.org/10.3126/njog.v6i2.6758